EFEKTIVITAS APLIKASI IDENTITAS KEPENDUDUKAN DIGITAL DALAM PELAYANAN PUBLIK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PEKANBARU TAHUN 2024 - Shabrina ,; Rico Purnawandi Pane (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This research is motivated by the low activation rate of the Digital Population Identity (IKD) application in Pekanbaru City, which in 2024 only reached 14% of the minimum target of 30% set by the Directorate General of Population and Civil Registration. The main issues include the lack of effective socialization to the public, low public understanding of the importance of the Digital Population Identity (IKD), frequent technical disruptions in the application, and the suboptimal use of the population document application service features thru the IKD application. This study aims to describe the effectiveness of the Digital Population Identity application in public services at the Pekanbaru City Population and Civil Registration Office in 2024 based on Campbell J.P's effectiveness theory, which includes five indicators: program success, target success, program satisfaction, input and output levels, and overall goal achievement. This research uses a qualitative approach with a descriptive type of study. Data were collected thru interviews and documentation using purposive sampling techniques involving the Disdukcapil and the community of IKD users. Data analysis was conducted thru the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the effectiveness of the IKD application at the Population and Civil Registration Service of Pekanbaru City as a whole has been running but is not yet optimally effective. This is reflected in the overall five assessed indicators, namely program success, target success, satisfaction with the program, as well as input and output levels, all of which indicate that they have not yet been optimally effective, resulting in the overall achievement of the IKD program's objectives also being ineffective. Therefore, it is necessary to strengthen socialization to the public, improve the technical stability of the application, and coordinate with the central government to encourage the acceptance of Digital Population Identity (IKD) across public service sectors. Keywords: Effectiveness, Digital Population Identity, Public Services